The Gut and Parkinson's Disease—A Bidirectional Pathway - Santos, Susanne Fonseca; de Oliveira, Hadassa Loth; Yamada, Elizabeth Sumi; Neves, Bianca Cruz; Pereira, Antonio (Frontiers in Neurology, 2019)
Humans evolved a symbiotic relationship with their gut microbiome, a complex microbial community composed of bacteria, archaea, protists, and viruses, including bacteriophages. The enteric nervous system (ENS) is a gateway for the bidirectional communication between the brain and the gut, through the vagus nerve (VN). Environmental exposure plays a pivotal role in the composition and functional capacity of the gut microbiome and may contribute to susceptibility to neurodegenerative disorders, such as Parkinson’s disease (PD). The neuropathological hallmark of PD is the widespread appearance of alpha-synuclein aggregates (SNCA) in both the central and peripheral nervous systems, including the ENS. Many studies suggest that gut toxins can induce the formation of SNCA in the ENS, which may then be transmitted in a prion-like manner to the CNS through the VN. PD is strongly associated with aging and this may reflect the accumulative effect of neurotoxicant exposure on SNCA pathology. In the present work, we revisit some landmark discoveries in the field of Parkinson’s research and focus on the gut-brain axis. In the process, we highlight evidence showing gut-associated dysbiosis and related microbial-derived components as important players in the increased risk of PD. The gut microbiome emerges as a potential target for protective measures aiming to reduce the risk of PD onset.